Numerical simulation of static tensile testing - Aung, Thet Paing (Nanyang Technological University, 2021)
Computer simulation has increased in popularity as technology advances. The successful simulation will not only improve the product development cycle but also reduce the time, cost and provides a safer working environment. This Final Year Project Report aimed to present the numerical simulation of tensile testing using Finite Element Method (FEM). A quasi-static test has used to investigate the specimen at a slower strain rate condition. ANSYS, one of the commercial FEA software packages has used to simulate the tensile test of aluminium alloy Al 6061-T6 specimen. The specimen was first modelled in CAD software, Solidworks then transferred to ANSYS mechanical to perform the simulation. Both Bi-Linear and Multi-Linear Isotropic Hardening models were used to study the Quasi-static simulation and results were compared with the experimental data. Simulation with imperfect geometry was also investigated and results were discussed for possible corroboration.